Environmental magnetic studies on surface sediments: a proxy for metal and hydrocarbon contamination - Venkatachalapathy, R.; Rajeswari, V.; Basavaiah, N.; Balasubramanian, T. (My University, 2014)
Visakhapatnam is one of the major port cities, and it is developed into a hub of many large- and medium-scale industries. Due to growing industrialization and urbanization, coast is vulnerable to both organic and inorganic micro-pollutants. Twenty-five surface sediments were collected along the Visakhapatnam coast for the measurement of texture size, petroleum hydrocarbons, trace metals and environmental magnetic parameters. The percentage of coarser particles was more in the northern region, whereas the percentage of fine particles was increased toward south. Elevated levels of petroleum hydrocarbons and trace metals were attributed due to marine and land-based sources, in particular, those were due to shipping activities, treated and partially treated sewage and industrial wastes. The concentrations of trace metals, petroleum hydrocarbons and magnetic minerals were decreased from nearshore to seaward. Our results revealed that the magnetic mineralogy is dominated by magnetite with a small proportion of hematite, and the grain size of magnetic minerals was in the range of pseudo-single domain to multidomain nature with detrital origin. From the principal component analysis, the magnetic concentration and mineralogy-dependent parameters co-vary with the heavy metal and PHC concentrations, suggesting that the inputs of magnetic minerals, petroleum hydrocarbons and heavy metals in the Visakhapatnam shelf sediments were derived from the same anthropogenic sources. Thus, the large magnetic dataset can be used to reduce the number of chemical analysis; hence, environmental magnetic parameters were used as a proxy for both organic and inorganic micro-pollutants.
Keywords: Environmental magnetism; Sediment texture; Petroleum hydrocarbon; Trace metals; Multivariate statistics